Mobile shopping apps adoption and perceived risks: A cross-country perspective utilizing the Unified Theory of Acceptance and Use of Technology. (September 2018) - Chopdar, Prasanta Kr.; Korfiatis, Nikolaos; Sivakumar, V.J.; Lytras, Miltiades D.
Abstract: Consumer adoption of mobile shopping apps is an emerging area in m-commerce which poses an interesting challenge for retailers and app developers. In this study, we adapt the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) to investigate factors predicting consumer behavioral intention (BI) and use behavior (UB) towards mobile shopping apps, considering the impact of two manifestations of consumer's perceived risk: Privacy Risk and Security Risk. Because cultural characteristics may moderate the impact of these risks on behavioral intention and use behavior, we conduct two studies from two consumer panels from countries with significant difference in technology use as captured by the Computer-Based Media Support Index (CMSI), namely India (high CMSI) and USA (low CMSI). For both countries, the baseline UTAUT 2 constructs predict the Behavioral Intention to use mobile shopping apps (and subsequently use behavior). However, the manifestations of perceived risk are significant only for the country with the highest CMSI score, suggesting that cultural influences play a strong role in the adoption of m-shopping. Our study has practical implications for theory as it poses the use of m-shopping apps in a cross-cultural context, suggesting that privacy and security moderate intention to use differently across cultures as predicted by the CMSI. From that perspective, it also has practical implications for consumer behavior researchers and app developers challenged with app localization as well as retailers designing mobile shopping apps for an intercultural audience. Highlights: The suitability of UTAUT2 on explaining adoption of m-shopping apps is examined. Perceived Privacy and Security risks are added to UTAUT2. We conduct two studies in India and USA using consumer panels. We find that perceived risks are affecting m-shopping app adoption in India. Results add to the discussion of adoption stages for developed vs emerging markets.